Analisis Manajemen Limbah Konstruksi Untuk Konstruksi Berkelanjutan (Studi Kasus Pembangunan Perumahan Family 100 di Denpasar) - Made Anom Dwiadnya Adipta; I Komang Agus Ariana; I Gusti Ngurah Putu Dharmayasa; I Gusti Agung Ananda Putra; I Ketut Nuraga (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Rapid development in the construction sector often generates large amounts of waste that negatively impact the environment and project efficiency. This study aims to analyze construction waste management in support of sustainable construction, with a case study on the Family 100 Housing development project in Denpasar. The research method used was descriptive quantitative with data collection through observation, interviews, and distribution of questionnaires to 30 respondents consisting of related parties in the project. The data was analyzed using Microsoft Excel based on the parameters of the Green Building Council Indonesia (GBCI) version 1.1 of 2016. The results show that the most dominant type of waste produced is residual materials such as concrete, wood, and plastic. Waste management practices include reuse, resale, and recycling. Despite some good waste management efforts, there are still discrepancies with some GBCI parameters. This study concludes that construction waste management in the Family 100 Housing project has begun to lead to sustainable practices, but improvements are still needed in formal policies and supporting facilities to be more in line with green construction principles. This research is expected to be a reference for contractors and stakeholders in implementing effective and environmentally friendly construction waste management